The Use of Mirror Therapy in Peripheral Seventh Nerve Palsy: A Systematic Review - Marco Castaldo; Giovanni Sellitto; Ilaria Ruotolo; Anna Berardi; Giovanni Galeoto (Brain Sciences, 2024)
Background: Conservative therapy is currently the elective treatment for peripheric facial palsy according to scientific literature. The success of conservative therapy is due to physiotherapy and the application of its methods. The aim of this systematic review was to assess mirror therapy, a physiotherapeutic method. Objectives: The aim of the following systematic review is to evaluate the effectiveness of using mirror therapy in patients with peripheral paralysis of the seventh cranial nerve. Methods: This systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The screening of literature was carried out on Cochrane, PEDro, PubMed/Medline, Scopus and Web of Science databases up until August 2022. All studies were randomized controlled trials (RCTs) and 5 articles met the inclusion criteria and were included in this study. The risk of bias was evaluated with PEDro and Jadad scales. Discussion: In the present study, we reviewed 5 RCTs that compared mirror therapy with other physiotherapy treatments or placebo to reduce pain, depression and improve range of motion in patients with peripheric facial nerve palsy. Conclusions: Further studies are needed to determine the effectiveness of this type of treatment, but nevertheless the data obtained are very encouraging.